Learning with fixed rules: the minority game - Kets, W (Wiley, 2011)
This paper gives a critical account of the literature on adaptive behaviour in the minority game, a simple congestion game. The literature has proposed a model which differs markedly from many standard learning models in that players are endowed with a fixed subset of behavioural rules or response modes which map the observed history to actions. These rules need not have a behavioural interpretation or be derived from some form of optimizing behaviour. Nonetheless, this model gives rise to behaviour that is close to equilibrium behaviour at the aggregate level. The individual‐level behaviour predicted by the model seems to capture some aspects of observed experimental behaviour that are difficult to explain using standard models.